Domiciliary noninvasive positive airway pressure therapy in children. Issue 4 (14th December 2015) - Amin, Reshma; Al‐Saleh, Suhail; Narang, Indra
SUMMARY: There has been a dramatic increase in the past few decades in the number of children receiving noninvasive positive airway pressure (PAP) therapy at home. Although PAP therapy was first prescribed for children with obstructive sleep apnea, the indications have rapidly widened to include treatment for central hypoventilation syndromes, neuromuscular and chest wall disorders as well as primary respiratory diseases. Given the rapidly expanding use of PAP therapy in children, pediatric pulmonologists need to be familiar with the indications, technical and safety considerations as well as potential complications and challenges that may arise when caring for children using PAP therapy. This review article covers the definition of PAP therapy, modes, interfaces, devices, indications, contraindications, suggested settings, complications as well as the factors influencing the adherence.Pediatr Pulmonol. 2016;51:335–348 . © 2015 Wiley Periodicals, Inc.